Climate Change and Mental Health: An Interactive Educational Session - Andrea Costin; Daniel Fisher; Bethany Harper; Ramzi W. Nahhas; John Sullenbarger (Association of American Medical Colleges, 2024)
Introduction Climate change is the single biggest health threat facing humanity, with direct and indirect impacts on mental health, yet health impacts of climate change remain notably absent from most medical school curricula. We describe a timely interactive educational session on climate change and mental health that was implemented and studied on a medical student clinical psychiatry rotation. Methods We developed a 1-hour introductory session on the mental health impacts of climate change and potential solutions. The session was delivered to third-year medical students on their 4-week clinical psychiatry rotation and included pre- and postsession survey questions assessing their knowledge, comfort, and readiness regarding the topic. Results Seventy students participated in the session, with 49 students completing the pre- and postsession surveys, giving a response rate of 70%. The average score for the four Likert-scale questions on the survey increased from 2.7 presession to 3.9 postsession on a 5-point scale (1 = strongly disagree, 5 = strongly agree). All questions displayed statistically significant improvement. Qualitative analysis identified knowledge gained about the mental health impacts of climate change as the most important aspect of the session to students. Discussion The introductory session effectively filled an urgent need in medical education curricula regarding climate change's effects on human health. Overall, distribution of and improvement upon this timely teaching content can serve a valuable role in medical student education as the effects of climate change, particularly on mental health, continue to progress throughout the century.